PENGARUH PROFITABILITAS, SOLVABILITAS, DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING - Sauvika, Vara (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
This research is aimed to analyze the influence of profitability, solvability and liquidity for dividend policy using Good Corporate Governance (GCG) as the intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI). In this research, the kind of data used is quantitative and the data source is secondary data in the form of annual report of manufacturing companies at 2008-2012. The sampling method is based on the method of purposive sampling. The samples used are 9 of 148 companies registered on Indonesia Stock Exchange (BEI). The variable used is independent variables, they are ratio profitability by using return on equity (ROE), solvability by using debt to equity ratio (DER), and liquidity by using current ratio (CR) with the dependent variables are dividend policy by using dividend payout ratio (DPR) and intervening variable (composition of board of commissioners and board of directors). Data analysis method used is multiple linear regression and path analysis. The result showed ratio profitability by using return on equity (ROE), solvability by using debt to equity ratio (DER), composition of board of commissioners and board of directors influenced the dividend policy significantly meanwhile the liquidity of ratio (CR) did not influence the dividend policy. By using path analysis, the research finding showed Good Corporate Governance (GCG) was the intervening variable. Further researchers are expected to give additional independent variable such as cash flow variable and control variable such as the standard of company to improve the correlation between dividend policy and Good Corporate Governance (GCG).